2021
DOI: 10.1021/acs.jpca.1c02516
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Potassiumtert-Butoxide-Catalyzed Ketones Hydrogenation in the Solution Phase

Abstract: The mechanism of ketones homogeneous hydrogenation with t-BuOK in tert-butanol is currently portrayed as the one proceeding via a six-membered [2 + 2 + 2] cyclic transition state involving the H2 molecule, the base, and a ketone. However, the concerted nature of the reaction is inconsistent with a number of experimental observations. Here we reanalyze available experimental data and revise the mechanism of this paradigmatic reaction based on the static and dynamic density functional theory (DFT) calculations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…This confirms the significant role of K + ions in the present reaction. In addition, to check any possible metal contamination, [38] i. e. the leading force of the reaction, ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) of each chemical used was performed and only rather insignificant 1.8, 1.3, 0.1, 0.8 ppm level of copper, nickel, manganese and silver ions were detected, [39] while other metal ions are below the detection level. To completely rule out the possible impurity effect, we carried out two similar reactions using new glassware and stirring bars under standard reaction conditions, where we intentionally added a catalytic amount of transition metal salts (0.1 mg of NiCl 2 , CuSO 4 , PdCl 2 , RuCl 3 ) into one of the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms the significant role of K + ions in the present reaction. In addition, to check any possible metal contamination, [38] i. e. the leading force of the reaction, ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) of each chemical used was performed and only rather insignificant 1.8, 1.3, 0.1, 0.8 ppm level of copper, nickel, manganese and silver ions were detected, [39] while other metal ions are below the detection level. To completely rule out the possible impurity effect, we carried out two similar reactions using new glassware and stirring bars under standard reaction conditions, where we intentionally added a catalytic amount of transition metal salts (0.1 mg of NiCl 2 , CuSO 4 , PdCl 2 , RuCl 3 ) into one of the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms the significant role of K + ions in the present reaction. In addition, to check any possible metal contamination, [38] i. e . the leading force of the reaction, ICP‐OES (Inductively Coupled Plasma Optical Emission Spectroscopy) of each chemical used was performed and only rather insignificant 1.8, 1.3, 0.1, 0.8 ppm level of copper, nickel, manganese and silver ions were detected, [39] while other metal ions are below the detection level.…”
Section: Resultsmentioning
confidence: 99%
“…Toluene was degassed by three freeze–pump–thaw cycles and used without drying. The gas chromatography mass spectrometry (GC‐MS) analysis of the reaction mixtures (no work up) detects 4 as the only product when KO t Bu, [18] a 1 : 1 mixture of KO t Bu and Et 3 SiH, [19,20] potassium bis(trimethylsilyl)amide (KHMDS), or a commercial silica‐supported sodium‐potassium alloy K 2 Na/SiO 2 are used [21] . However, the molar amounts of 4 correspond to merely 1–10 % of the used potassium reagents (Table 1, entries 1–4) [22] .…”
Section: Resultsmentioning
confidence: 99%
“…One of the main features of the code is the Quickstep module, allowing for the use of both atom-centered Gaussian orbitals and plane waves as a basis for the solution of the Schrödinger equation. This feature helps when analyzing large systems such as liquid solutions or chemical reactions with the explicit inclusion of solvent molecules . Even with the use of the most optimized features of CP2K, it can still take weeks to complete a simulation at scale, thus the need for even more performance optimization.…”
Section: Introductionmentioning
confidence: 99%
“…This feature helps when analyzing large systems such as liquid solutions or chemical reactions with the explicit inclusion of solvent molecules. 12 Even with the use of the most optimized features of CP2K, it can still take weeks to complete a simulation at scale, thus the need for even more performance optimization. This study analyzed the multilevel parallel performance of the CP2K code on CPUs and GPUs for a case study of the intermediate complex found in the catalytic Milstein ester hydrogenation reaction in methanol.…”
Section: ■ Introductionmentioning
confidence: 99%